CAN ATHLETIC PERFORMANCE TESTS IN FEMALE SOCCER PLAYERS BE A CRITERIA IN BEING ELECTED IN NATIONAL TEAM? - Şahin, Mustafa (Acta Scientiae et Intellectus, 2024)
The aim of this study is to reveal Turkey Soccer Federation (TFF) Women League 1 club team athletes’ physical performance differences between athletes who have played in A team and stayed in national level. A total of 18 athletes who competed in the women's soccer league, whose ages between 18-30, (National team sportsman n = 8; n = 10) participated. The Yo-Yo Intermittent Recovery Test Level 1 (YOY IRT1) endurance tests, the players' age, height, body weight, body mass index (BMI), standing long jump with double and one foot and 5-10-30m speed test were conducted. The measurements were carried out at the 17th week of the competition. The statistical analysis of the study was made by using the SPSS 21.0 packaged program, and the Mann Whitney U test was applied to the comparison of the soccer players elected and not elected. The statistical significance level was accepted as 0,05. When soccer players’ performance tests were compared according to being elected or not elected to the national team, no statistically significant difference was found (p>0,05). As a result, Turkey's athletic performance status in women's soccer at the elite level, can be said to be similar in elected and not elected athletes to the national team.